2016
DOI: 10.1039/c6ay00454g
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical sensing of the antimicrobial drug linezolid utilising an electrochemical sensing platform based upon a multiwalled carbon nanotubes/bromocresol green modified carbon paste electrode

Abstract: The electroanalytical sensing of linezolid is reported using a multiwalled carbon nanotubes (MWCNTs)/bromocresol green (BCG) modified carbon paste electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…modified a glassy carbon electrode surface with electrochemically reduced graphene oxide‐bentonite composite material and used the absorptive stripping differential pulse voltammetry technique to obtain an LOD value of 0.0337 μM. Another study by Mohamed et al . modified a carbon paste electrode surface with multi‐walled carbon nanotubes‐bromocresol green and found an LOD value of 7.57 x 10 −3 μM.…”
Section: Introductionmentioning
confidence: 99%
“…modified a glassy carbon electrode surface with electrochemically reduced graphene oxide‐bentonite composite material and used the absorptive stripping differential pulse voltammetry technique to obtain an LOD value of 0.0337 μM. Another study by Mohamed et al . modified a carbon paste electrode surface with multi‐walled carbon nanotubes‐bromocresol green and found an LOD value of 7.57 x 10 −3 μM.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology has become one of the most attractive disciplines in science and technology nowadays. The deep interest in nanotechnology is being motivated by various remarkable fields and is leading to a new manufacturing up rising . Nano‐materials such as carbon nanotubes, nanoparticles, or nanocomposite connected with biomolecules are being used for several bioanalytical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐materials such as carbon nanotubes, nanoparticles, or nanocomposite connected with biomolecules are being used for several bioanalytical applications . Electrochemical methods of analysis have shown to be accurate, sensitive and cost‐effective . Nanocomposite of a variety of shapes, sizes and compositions are changing now a days the bioanalytical measurement.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhou et al reported a label-free determination of lead ions by decorated gold nanoparticles on the surface of ordered mesoporous carbon. [38][39][40][41] However, the paraffin oil used as the conventional organic liquid is a non-conductive material, which to some extent attenuates the electrochemical performance of the CPE. 25 In addition, Yang et al utilized a Prussian blue/ ordered mesoporous carbon composite as a conductive support for the preparation of a metolcarb imprinted sensor.…”
Section: Introductionmentioning
confidence: 99%